1981-1982 ネン マクマードサウンド チイキ ノ コクサイ キョウドウ カンソク - 渋谷, 和雄; シブヤ, カズオ; 岡山, 宗夫; オカヤマ, ムネオ; 寺井, 啓; テライ, ケイ; Shibuya, Kazuo; Okayama, Muneo; Terai, Kei (1984)
P(論文) 前年度に引き続き, 西南極エレバス火山において火山性地震の観測を行った。テレメーター地震観測点をエレバス山頂に1点, 山腹を取り巻くように3点設置した。また, テラ山山頂にも地震計を1点設置して, ロス島東部の地震活動を監視することにした。さらに前年同様, エレバス山頂では, 噴火を監視するための磁気誘導ループセンサー, 低周波音波センサーをおいて継続観測している。テレメーター受信側の点検整備として, FM復調分別器の増設, FM磁気記録計, ペン書き記録計の保守と記録系時計の交換, 雑音対策などを行った。テレメーター網の整備後, 5台の直接録音方式アナログ記録計をエレバス山腹に展開し, 多点集中観測を試みた。記録計1台が故障したが, テレメーター観測点と合わせ8点が同時作動している期間が7日, 7点が同時作動している期間は19日であった。臨時観測点設置にあたっては, 1点につき20-30分の作業時間で観測が開始でき, 飛行回数1回, 地上待機を含めて10時間のヘリコプター支援で, 5点が展開可能なことが確かめられた。 Observation of volcanic earthquakes was continued on Mount Erebus, Antarctica, by maintaining 3 telemetering seismic stations installed in the 1980-1981 field season. Two telemetering stations were newly installed on the flank of Mount Erebus and on Mount Terror. Observation of magnetic induction loop and infrasound which might be associated with volcanic eruption was also continued at the summit of Mount Erebus. In order to reduce noises in the time signal, the recording-system clock at Scott Base was replaced by the electrically shielded time code generator. Five temporary seismic stations were installed on the flank of Mount Erebus after the maintenance of the telemetering system. Constitution of a densely located network of 7-8 stations with the aperture of 5-10km will enable us to obtain rather accurate hypocenter parameters of shallow earthquakes with 0-3km focal depth. departmental bulletin paper